Brain magnetic resonance imaging findings in Mitochondrial Neurogastrointestinal Encephalomyopathy (MNGIE): A case-based review - Maria Veatriki Christodoulou, MD, MSc; Nikoletta Anagnostou, MD, MSc; Anastasia K. Zikou, MD, PhD (Radiology Case Reports)
Mitochondrial neurogastrointestinal encephalopathy (MNGIE) is a rare autosomal recessive disorder, manifesting with gastrointestinal dysmotility, cachexia, ptosis and peripheral neuropathy. Diffuse leukoencephalopathy in brain MRI is a hallmark of MNGIE. We report a case of a 21-year-old female with MNGIE, presenting with cachexia and chronic diarrhea. Brain MRI revealed lesions in the cerebral deep white matter and the pons, with sparing of the subcortical U-fibers and the cerebral cortex and no apparent involvement of the cerebellum, basal ganglia, and thalamus. A literature review led to the identification of 72 additional cases with MNGIE that underwent brain MRI. Leukoencephalopathy of the cerebral white matter was present in all but 2 patients. The objective of this study is to increase radiologists' awareness of this challenging-to-diagnose disease, as well as to demonstrate the value of advanced MRI techniques in understanding the underlying pathology. The presence of leukoencephalopathy on brain MRI in patients with cachexia and neurological manifestations, should raise the suspicion for MNGIE and trigger further biochemical and genetic testing.